1917 Iowa Acts 185, An Act . . . relating to burglary with explosives and to enact a substitute therefor, relating to burglary with explosives and electric burning, and gun, § 1 - (:unkn) unknown (General Publisher, 1917)
Enhanced the sentence of any person who breaks and enters any dwelling and opens a vault, safe, or other secure place by use of nitro-glycerine, dynamite, giant powder, gunpowder, or any other explosive material.
--
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME